45 Utilization of thrombolysis in the national ACS programme: the cork university hospital experience. (16th October 2019) - Sharif, Z; Fitzgerald, G; Curtin, R; Kearney, P; McFadden, E; O' Connor, P; Kelly, P; Vaughan, C; Curtain, J
Abstract : Background: Optimal Reperfusion in STEMI is the key goal of the National ACS Programme. The aims of the programme are a diagnosis to door time [DDT] <90 minutes and a diagnosis to reperfusion time of <120 minutes with a goal of Primary PCI (PPCI) as the method of reperfusion in 80% STEMIs. Thrombolysis is an important reperfusion strategy where primary PCI cannot be offered to STEMI patients within these recommended times. Aims: The purpose of this study was to examine the number of patients outside the recommended time goals being referred to Cork University Hospital (CUH) from other hospitals and hence to estimate the potential patient cohort that should be considered for thrombolysis prior to transfer to the Primary PCI centre, to identify the reasons why thrombolysis was not commenced and outcomes between those treated by guidelines versus those who were not. Methods: Consecutive patients from January 2016 to December 2017 diagnosed as STEMI or transferred to CUH as part of the National ACS Programme were identified. Patients initially referred to CUH from University Hospital Kerry and appropriately advised to refer to Limerick were excluded. Results: 451 patients met CODE STEMI acceptance criteria at CUH within the study period of which 79% were male, with an average age of 63 year. 104 patients were transfers from other hospitals within the PPCI catchment area. 34/451 (7.5%) patients were thrombolysed, 5/34 of which underwent rescue PCI (table 1). The mean time between diagnostic ECG and thrombolysis was 105.4 minutes. 1/34 cases thrombolytic therapy was administered within 10 minutes of STEMI diagnosis. 32/34 survived to discharge [Both deaths had delay until thrombolysis], 30-day and 1-year mortality were both 5.9%. Mean Left ventricular ejection fraction (LVEF) where measured was 42±10%. 7/34 had ventricular arrhythmia (2 in the context of resuscitated out of hospital cardiac arrest pre diagnosis), 0/34 had mechanical complications. 55/451 (12.2%) Patients had DDT > 90 minutes [average 118±62 minutes] and were not thrombolysed; 17/53 were transfers from other hospitals. 52/55 survived to discharge. Of those who underwent PPCI 30-day and 1 year mortality was 6 and 10% respectively. Mean LVEF was 41.6±9%. 8/55 had ventricular arrhythmia. 2/55 were in cardiogenic shock, 2/55 suffered mechanical complications of their ACS. Compared to those were accepted for PPCI with DDT < 90 minutes; 331/362 survived to discharge. 43 Ultimately did not have PPCI. Of those who underwent PPCI 301/319 survived to discharge, 30-day and 1 year mortality was 4.7 and 5.6% respectively. Mean LVEF was 43.6±12.9%. Conclusion: Compared to patients who underwent PPCI with a DDT < 90 minutes these patients with DDT > 90 minutes had a trend to inferior outcomes at one year (p=0.23). Delay until thrombolysis was common in our group undergoing thrombolysis. Where diagnosis to door is over 90 minutes thrombolysis should be administered if no contraindications in a time critical fasion. PPCI remains the method of reperfusion in >80% STEMIs referred to CUH.